Evaluating the Mechanisms of Landscape Change on White‐Tailed Deer Populations. Issue 2 (24th November 2020) - Laurent, Maud; Dickie, Melanie; Becker, Marcus; Serrouya, Robert; Boutin, Stan
ABSTRACT: Understanding how landscape change influences the distribution and densities of species, and the consequences of these changes, is a central question in modern ecology. The distribution of white‐tailed deer ( Odocoileus virginianus ) is expanding across North America, and in some areas, this pattern has led to an increase in predators and consequently higher predation rates on woodland caribou ( Rangifer tarandus caribou )—an alternate prey species that is declining across western Canada. Understanding the factors influencing deer distribution has therefore become important for effective conservation of caribou in Canada. Changing climate and anthropogenic landscape alteration are hypothesized to facilitate white‐tailed deer expansion. Yet, climate and habitat alteration are spatiotemporally correlated, making these factors difficult to isolate. Our study evaluates the relative effects of snow conditions and human‐modified habitat (habitat alteration) across space on white‐tailed deer presence and relative density. We modeled deer response to snow depth and anthropogenic habitat alteration across a large latitudinal gradient (49° to 60°) in Alberta, Canada, using motion‐sensitive camera data collected in winter and spring from 2015 to 2019. Deer distribution in winter and spring were best explained by models including both snow depth and habitat alteration. Sites with shallower snow had higher deer presence regardless of latitude. Increased habitat alteration increased deer presence in the northern portion of the study area only. Winter deer density was best explained by snow depth only, whereas spring density was best explained by both habitat alteration and the previous winter's snow depth. Our results suggest that limiting future habitat alteration or restoring habitat can alter deer distribution, thereby potentially slowing or reversing expansion, but that climate plays a significant role beyond what managers can influence. © 2020 The Wildlife Society. Abstract : In Alberta, Canada, sites monitored using motion‐sensitive cameras between 2015 and 2019 were more likely to have deer present with shallower snow and increased habitat alteration. At sites where deer were present, density was higher in areas with lower snow in winter but with greater habitat alteration in spring. Our results suggest that restoring habitat and limiting future habitat alteration can partially control deer distribution but that climate plays a significant role beyond what managers can influence.